فعالية الارشاد المدرسي في مواجهة العنف المدرسي لدى تلاميذ المرحلة المتوسطة من وجهة نظر المستشاريين مهنيين - أمال صواطي; فاطمة الزهرة طالب; بدرية النوعي (My University, 2021)
This study is focused on the effectiveness of school counseling in the fight against school violence among middle school students. The study is taken from the counselors' point of view. This study was conducted at the Vocational Guidance Center in Laghouat. The study was conducted in the month of May 2021 and the descriptive exploratory approach was used. The sample of the study included 12 consultants, and the study tool was open-ended questions. Finally, the study results in the following ideas: The guidance counselor has a role in reducing the phenomenon of school violence. The guidance counselor is interested in monitoring and treating various forms of school violence. 1. School counseling. 2. School violence